Bragg reflection and transmission of light by one-dimensional gyrotropic magnetophotonic crystal - Shmat'ko, A. A.; Mizernik, V. N.; Odarenko, E. N.; Rokhmanova, T. N. (IEEE, 2017)
Reflection and transmission coefficients for onedimensional magnetophotonic crystal with a bilayer unit cell are obtained in analytical form. The bilayer consists of arbitrary gyrotropic media. Analytical dispersion equation for gyrotropic multilayer periodic structure is obtained. Different regimes of bulk and surface wave’s propagation in structure layers are investigated. System parameters values that correspond to both total reflection and total transmission by gyrotropic Bragg structure are found. The possibility of band structure controlling with an external magnetic field is shown.
Keywords: magnetophotonic one-dimensional crystal; gyrotropic media; ferrite with transversal magnetic field; dispersion characteristics; band gap